2019
DOI: 10.3748/wjg.v25.i26.3426
|View full text |Cite
|
Sign up to set email alerts
|

International normalized ratio and Model for End-stage Liver Disease score predict short-term outcome in cirrhotic patients after the resolution of hepatic encephalopathy

Abstract: BACKGROUND In patients with cirrhosis, hepatic encephalopathy (HE) indicates a poor prognosis despite the use of artificial liver and liver transplantation, presenting as frequent hospitalizations and increased mortality rate. AIM To determine predictors of early readmission and mid-term mortality in cirrhotic patients discharged after the resolution of HE. METHODS From January to February 2018, 213 patients were enrolled in this observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Similarly, HE is also an important feature of liver failure. Once HE occurs in patients with chronic liver disease, the prognosis is very poor, with a 1-year survival rate of less than 50% and a 3-year survival rate of less than 25%[ 46 ]. Studies have shown that INR is associated with the death of patients with cirrhosis[ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, HE is also an important feature of liver failure. Once HE occurs in patients with chronic liver disease, the prognosis is very poor, with a 1-year survival rate of less than 50% and a 3-year survival rate of less than 25%[ 46 ]. Studies have shown that INR is associated with the death of patients with cirrhosis[ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once HE occurs in patients with chronic liver disease, the prognosis is very poor, with a 1-year survival rate of less than 50% and a 3-year survival rate of less than 25%[ 46 ]. Studies have shown that INR is associated with the death of patients with cirrhosis[ 46 , 47 ]. Moreover, a serum sodium imbalance is very common in cirrhotic patients with AKI and affect the prognosis of these patients[ 48 - 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the study conducted by Koch et al, the INR level was found to be longer than normal in cases with HE resulting in death (16). In a study conducted in China, it was found that the high INR value at discharge after HE predicts readmission to the hospital and this may be associated with mortality (17). When the prolongation of aPTT, PT and INR levels among hemostasis parameters is considered in terms of mortality in patients with HE, it emerges as an important parameter.…”
Section: Discussionmentioning
confidence: 83%
“… 14 Hu et al noted in their study that INR at discharge (>1.62) independently predicted overall readmission after index PSE, and that the MELD score was the only variable that predicted readmission specifically because of PSE. 15 INR has been associated with a longer hospital stay in PSE patients. However, it did not significantly differ in our particular study.…”
Section: Discussionmentioning
confidence: 97%